2015
DOI: 10.24114/jt.v12i2.3248
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Ajar Fisika Berbasis Inkuiri Pada Materi Fluida Statis Untuk Meningkatkan Hasil Belajar Siswa

Abstract: Penelitian ini bertujuan untuk menganalisis apakah bahan ajar yang dikembangkan dapat meningkatkan aktivitas, respon, dan hasil belajar siswa pada materi fluida statis berbasis inkuiri berdasarkan standart BSNP. Metode yang dilakukan dalam penelitian ini adalah penelitian pengembangan (Research and Development). Sampel penelitian ini adalah kelas X IPA2 SMA Swasta PRIMBANA Medan pada bulan Maret–April 2015 dengan jumlah siswa 30 siswa. Instrumen yang digunakan untuk mengumpulkan data yaitu 1) menggunakan lemba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Material is part important in the learning process that occupies a strategic position and can _ determine the success Study teacher and influence to performance Study child. This matter in line with (Pohan, LA, Situmorang, M., & Jahro, 2016) which states that Teaching materials are educational media as supporting and strengthening in the learning process. Whereas (Safitri, ER, & Nurkamilah, 2020b) opinion that digital teaching materials are integrated teaching materials information and technology computerization .…”
Section: Resultsmentioning
confidence: 56%
“…Material is part important in the learning process that occupies a strategic position and can _ determine the success Study teacher and influence to performance Study child. This matter in line with (Pohan, LA, Situmorang, M., & Jahro, 2016) which states that Teaching materials are educational media as supporting and strengthening in the learning process. Whereas (Safitri, ER, & Nurkamilah, 2020b) opinion that digital teaching materials are integrated teaching materials information and technology computerization .…”
Section: Resultsmentioning
confidence: 56%
“…The educational level chosen for the literature review are: articles to students of junior, senior/ vocational high school, and university. Two articles for students of junior high school (Maskhuliyah & Bungkang, 2017;Lepiyanto, 2011), 13 articles for senior high school (Sujanem, 2012;Sufinah et al, 2013;Landriany, 2014;Susilo et al, 2014;Tampubolon et al, 2015); and 50 articles for university students (Zuchdi et al, 2010;Parmin & Peniati, 2012;;Tannir & Al Hroub, 2013;Al Azri. & Al Rashidi, 2014;;Celik, 2014;Novian et al, 2014;Khaimar, 2015;Satriawan & Rosmiati, 2016); Fadilah et al, 2016;Nisrina et al, 2016;Komang et al, 2017;Maskhuliyah et al, 2017;Nihayah et al, 2018) as shown in Figure 4.…”
Section: Educational Stagementioning
confidence: 99%
“…Hal tersebut terlihat dari hasil belajar siswa yang rata-rata hanya mencapai 70% dari kriteria ketuntasan minimal (KKM). Tampubolon (2015) menjelaskan beberapa faktor yang menyebabkan siswa kesulitan memahami materi adalah sumber belajar seperti buku teks yang terbatas dan kurang interaktif sehingga siswa kurang tertarik untuk mempelajarinya. Kesulitan siswa dalam pembelajaran fisika dinyatakan pula oleh siswa pada lembar angket yang diberikan kepada 32 siswa.…”
Section: Pendahuluanunclassified